Aquatic insects assemblage in Penang Botanic Garden - Suhaila Ab Hamid; Siti Hamidah I.; Norshamiera Normi; Amila Faqhira Zainodin; Mohd Hafizul Hasmadi M.N. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2018)
This study investigated the diversity of aquatic insects as well as the chemical parameters of Sungai Air Terjun that runs in Penang Botanic Garden. Aquatic insects and chemical parameters of river were studied from April 2013 until January 2014. A total of twenty specimens were collected monthly using D and rectangular net following kick-net sampling technique. A total of 2966 individuals from 48 families of seven orders of aquatic insects were collected. The most abundant aquatic insects were recorded in July 2013 with 566 individuals from 44 genera, while the least abundant was in May 2013 with 156 individuals from 31 genera. The Diptera (996 individuals), Trichoptera (689 individuals) and Ephemeroptera (327 individuals) were very rich and diverse in this river during all the sampling months. This study provides a current situation of aquatic insect’s community and river condition of Sungai Air Terjun, Penang Botanic Garden.